Incidence of cervical cancer in young people and the socioeconomic profile of this group in the Regions of Brazil (Research, Society and Development, 2022)
Cervical cancer (CC), also called cervical cancer, is caused by infection with some types of Human Papillomavirus (HPV). CC is the third most frequent neoplasm in the Brazilian female population. The objective of the present study was to investigate the incidence of cervical cancer in young people and the socioeconomic profile of this group in the regions of Brazil. An exploratory literature review and qualitative method was carried out. Data collection was carried out by searching the following databases: SciELO, LILACS, MEDLINE, Google Scholar and PubMed. In the results, 13 articles were selected according to the objective proposed in this review. In the North region, there were higher mortality rates and higher growth rate due to cervical neoplasia in the South region. Recent data found in the literature showed that approximately 189 (0.68%) deaths occurred in women aged below 25 years. CC mortality in Brazil is still increasing in some Brazilian regions. These data reinforce previous studies that showed the main risk factors related to early initiation of sexual life, multiple sexual partners and lack of information about CC. Therefore, there is a need for greater action on public policies and educational practices that lead and encourage this young population to raise awareness of the prevention of cervical cancer according to the needs of each region, especially those most needy and with a low rate of education.